Tissue Culture and Agrobacterium-Mediated Transformation on Rosa Hybrida L. 'Christian Dior' - Kong, Swee Lan (1997)
Callus induction from leaf explants of Rosa hybrida L. 'Christian Dior' was established. Two types of auxins (2.4-D and NAA) at three concentrations (4.5, 9.0 and 13.5 µM) and two types of cytokinins (kinetin and BA) at three concentrations (2.3, 4.7 and 9.3 µM) were used in a 3 X 4 experimental design. The best caulogenesis and callus maintenance medium was 112 MS + 30 giL sucrose + 9.0 µM NAA + 2.3 µM BA cultured in the dark. Several attempts were carried out to induce shoot organogenesis and/or somatic embryogenesis from callus. None of the media tested induced shoots or somatic embryos. However, there were differences observed for callus growth on the medium tested. Combination of cytokinins (BA and TDZ) at 5.0-10.0 µM with auxins (NAA and IBA) at 1.0-2.0 µM, generally promoted callus proliferation. Callus cultured on cytokinin onlyAmino acids proline and glutamine also enhanced callus proliferation. Observations under the stereo microscope revealed that the callus was globular. Medium without ammonium ion enhanced callus proliferation. TDZ was found to be the better cytokinin for callus proliferation. Observation of cells taken from callus cultured on the various media revealed that there was no meristematic primordias . Agrobacterium-mediated transformation of R. hybrida L . 'Christian Dior' callus produced three transgenic callus lines that were confirmed by dot blot and Southern hybridisation assays. Leaf-derived callus was transformed with Agrobacterium tumefaciens LBA4404 carrying plasmid pBI 121 which contained the B-glucuronidase (GUS) gene and nptII gene coding for kanamycin resistance. The best condition for infection of callus tissues with A. tumefaciens was exposure to 1 X 1 09 cells/ml for 5 minutes. At this condition, GUS activity was found to be the highest (6.39 ± 0.01 pmol MU/h/p.g protein). It was also found that at low Agrobacterium concentration, increasing the exposure period increased GUS transient activity, and at high Agrobacterium concentration, increasing exposure period reduced GUS transient activity . Transformation efficiency improved when callus was cultured for 2 weeks on medium without kanamycin (but with 500 p.g/ml carbenicill in) before transferring the callus to medium with 300 p.g/ml kanamycin + 500 p.g/ml carbenicillin for selection. Carbenicillin served to eliminate Agrobaterium. Kanamycin was also found to be unsuitable for used as a selective marker.